DETENTION OF VISUAL PROBLEMS IN SCHOOL CHILDREN AND ADOLESCENTS - Alexandra Isabel Amorim Lino; Nicolly Helen F. Morais; Elisangela de S. Marques; Carmen Luci R. Lopes; Maria Alves Barbosa (Universidade Federal de Goias, 2003)
The precocious detention of visual problems is a measure of important primary assistance. Thus being,this work had as main objective, to verify the visual level of children and adolescents in Goiânia (Goiás Brazil)public school, being used the simplified physical examination of health through Snellen Table. Of the 414evaluated children, 46 (11%) had presented visual deficiency and had been directed for oftalmological consultationin the Hospital of the Clinics of the Federal University of Goiás.